L’inventario del palazzo di Giuseppe Tibaldi: musica e collezionismo nella Bologna di fine Settecento - Davide Mingozzi (Artes)
The definition of the tenor as the “primo uomo” emerged gradually beginning in the mid-18th century, and Giuseppe Tibaldi played a crucial role in this process. In the 1750s he embarked on a brilliant career alongside his wife, Rosa Tartaglini. His vocal style inspired the characters of Admeto in Gluck’s Alceste and Aceste in Mozart’s Ascanio in Alba. In addition to being a singer, Tibaldi was a respected composer and served multiple times as principe for the Accademia dei Filarmonici. He had a close friendship with Giambattista Martini, to whom he entrusted the education of his son Ferdinando. Other members of the Tibaldi family also performed on stage, including Pietro, Giuseppe’s brother, and his wife Angela Masi; Giuseppe and Carlo, the tenor’s second and third sons; and Costanza, Carlo’s daughter, who concluded the Tibaldi musical dynasty in the first half of the 19th century. The paper summarizes the Tibaldi family’s history across three generations, highlighting their educational and professional relationships. It presents a 1767 document with which Tibaldi purchased the family palace in Piazza Calderini and discusses the singer’s previously unknown will, accompanied by a detailed inventory of his substantial Bologna residence and rich musical library.